Residents’ Perspectives on Graduate Medical Education during the COVID-19 Pandemic and Beyond - William Rainey Johnson; David Blitzer (MedEdPublish, 2020)
Graduate medical education (GME) programs are saddled with the dual responsibilities of exceptional healthcare delivery, while ensuring their trainees' specialty-specific competency. The COVID-19 pandemic threatens this dual mission. The scarcity of resources has required redistribution of personnel, including trainees, and limitations on the number of personnel interacting with patients. These changes have lowered specialty specific clinical volume for trainees. GME programs must look for new ways to educate trainees. Failure to do so may lead to a bottleneck within the medical education training pipeline or graduation of less than fully competent physicians. As two GME trainees on the frontlines, we describe the negative impacts of the COVID-19 pandemic on current GME training in the United States. We then propose possible remedies to the problem. To account for lost training, we discuss potential solutions for filling gaps in training and, simultaneously, urge a coordinated effort among leaders in GME to use the pandemic to catalyze a revolution that will improving training now and in the future.